2010
DOI: 10.1007/s00404-010-1737-1
|View full text |Cite
|
Sign up to set email alerts
|

Does cervical length and the lower placental edge thickness measurement correlates with clinical outcome in cases of complete placenta previa?

Abstract: Short cervical length at cut-off value ≤30 mm and increased lower placental edge thickness measurements may predict with high accuracy the risk of APH and emergency preterm cesarean delivery in patients with complete placenta previa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 17 publications
4
43
0
Order By: Relevance
“…A short cervical length of less than 3 cm could predict the risk of antenatal hemorrhage (p=0.004). However, a short cervical length of less than 3 cm had no significant effect on cesarean hysterectomy and peripartum blood transfusion in their study [15]. Shin et al also reported the effect of cervical length on placenta previa.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…A short cervical length of less than 3 cm could predict the risk of antenatal hemorrhage (p=0.004). However, a short cervical length of less than 3 cm had no significant effect on cesarean hysterectomy and peripartum blood transfusion in their study [15]. Shin et al also reported the effect of cervical length on placenta previa.…”
Section: Resultsmentioning
confidence: 69%
“…Therefore, sonographic findings predicting preterm labor may be more meaningful for antenatal hemorrhage than sonographic findings predicting placental adhesion. Thus, it has been reported that cervical length in the third trimester of pregnancy is helpful for predicting antenatal bleeding [12,14,15]. However, Hasegawa et al did not attempt to measure cervical length [13].…”
Section: Resultsmentioning
confidence: 99%
“…28 Zaitoun et al reported similar findings regarding the value of cervical length as predictor of bleeding. 29 They found that patients with placenta previa and cervical length >30 mm had fewer emergency CD <36 weeks (10% versus 46%, p=0.002) and higher mean birth weights (2.8 versus 1.9 kg, p=0.003) as compared to those with cervical lengths ≤ 30 mm. Similar findings were reported by Fukushima et al where 77% of patients with placenta previa and cervical length >30 mm delivered >37 weeks as compared to only 50% of those with cervical length ≤ 30 mm who required emergency CD due to bleeding <37weeks' gestation (p=0.04); an additional finding was that a short cervix (≤ 30 mm) was associated with morbidly adherent placenta requiring cesarean hysterectomy in 35% of the cases as compared to only 6% in those with cervical length >30 mm (p=0.004).…”
Section: Discussionmentioning
confidence: 99%
“…29,31 Studies have shown that patients with placenta previa with "thick" placental edges over the internal OS (>1 cm thickness), as compared to those with thin placental edges over the internal OS (<1 cm) have a significantly higher frequency of APH episodes (3.8±1.6 versus 1.6±0.7), require more emergency CD <36 weeks (53% versus 26%; p=0.002), require more blood transfusions (2.4±2.6 versus 1.03±1.3 units; p=0.004), and have lower mean birth weight (1.93±0.47 versus 2.72±0.86 kg; p=0.006). 29,31 Present findings regarding a possible association between cervical length and trans cervical placental thickness measurement at 28-30 weeks gestation and the risk of emergent delivery in patients with PA have not been reported previously and may improve our ability to predict the clinical course and to refine obstetric management in these cases. If present data are confirmed on larger numbers, an earlier hospital admission or at least closer clinical monitoring in women with placenta previa and short cervix may become an option with delayed delivery with women with who deemed clinically stable in order to decrease the risks associated with prematurity.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of papers which already described the predicting factors of placenta previa including cervical length (3). Although several ultrasonographic findings of short cervical length are associated with bad consequences such as emergency CS, cesarean hysterectomy, intraoperative blood loss and placental adherence/accreta in patients with placenta previa (3)(4)(5)(6)(7), there is no research work describing the predictive value of the cervical length for pernicious placenta previa. Therefore, this study focused on the ultrasonographic findings of the cervix, and assessed their clinical usefulness as predictors for massive hemorrhage during a cesarean section in pernicious placenta previa.…”
Section: Introductionmentioning
confidence: 99%